Agro-morphological traits and SSR markers reveal genetic variations in germplasm accessions of Indian mustard – An industrially important oilseed crop. Issue 12 (December 2022) - Singh, Lal; Nanjundan, J.; Sharma, Deepika; Singh, K.H.; Parmar, Nehanjali; Jain, Rohit; Thakur, Ajay Kumar
Abstract: Indian mustard is an economic and highly important industrial oilseed crop. In this study, genetic diversity among 135 Indian mustard germplasm accessions was evaluated using 11 agro-morphological descriptors and 227 SSRs. Morphological characterization of Indian mustard germplasm accessions exhibited a broad range of variation for characters including biological yield (CV = 25.63%), seed yield (CV = 23.23% and 1000-seed weight (CV = 23.14%); whereas traits such as days to maturity (CV = 2.91%) showed lowest degree of variation. Out of 227 SSR markers evaluated, a total of 159 (70.04%) SSRs produced polymorphic products and 68 (29.96%) SSRs resulted into monomorphic amplicons. The polymorphic markers amplified 575 alleles and the number of alleles ranged from 2-7 with 3.61 average number of alleles per locus. SSR markers BRMS-030, Ra2-E11, Ra2-G05, Ni4-G10 and Ol10B11 generated the highest number of alleles (7). SSR marker Ra2-G05 was having the highest allele frequency (0.84), while BRMS-002 was having the lowest major allele frequency (0.33). Polymorphism information content (PIC) values ranged from 0.24-0.61 with an average value of 0.39 per primer pair. Unweighted pair group method with arithmetic mean (UPGMA) cluster analysis based on morphological traits grouped Indian mustard genotypes into three clusters, while two clusters were obtained based on SSR based clustering. Population structure analysis provided a better estimate of genetic diversity and divided all the genotypes into five subpopulations. Genetically diverse accessions identified may be used for hybridization in Indian mustard crop improvement programs in future. Abstract : Brassica juncea, Genetic diversity, Agro-morphological traits, SSR markers, Population structure.